Stargardt misdiagnosis: How ocular genetics helps. Issue 3 (24th December 2020) - Ibanez, Manuel Benjamin; de Guimarães, Thales Antonio Cabral; Capasso, Jenina; Bello, Nicholas; Levin, Alex V.
Abstract: Ocular Genetics at Wills Eye Hospital sees a wide range of rare disorders for accurate diagnosis. To demonstrate how focused consultation and genetic testing results in precise diagnoses, we investigated false diagnosis rates for patients referred with a diagnosis of Stargardt disease. This is a retrospective review of patients over a 3 year period referred to our Ocular Genetics clinic for possible Stargardt disease, or already holding a diagnosis of Stargardt disease. Results of diagnostic and genetic testing were compared to standard definition of Stargardt. Of 40 patients, 14 (35%) had been misdiagnosed. Four had non‐Stargardt phenotype of which three had ABCA4 pathogenic variants with phenotypes inconsistent with Stargardt disease. Two of those with pathogenic ABCA4 variants were related. Nine had pathogenic variants in other different genes with overlapping features of Stargardt disease. One had Thioridazine maculopathy. Our study highlights the essential role of the subspecialty field of ocular genetics in obtaining accurate diagnoses for the delivery of correct counseling and interventional trial eligibility assessment.